2006
DOI: 10.1073/pnas.0605563103
|View full text |Cite
|
Sign up to set email alerts
|

Pygmoid Australomelanesian Homo sapiens skeletal remains from Liang Bua, Flores: Population affinities and pathological abnormalities

Abstract: Indonesia ͉ microcephaly ͉ skeletal pathology ͉ asymmetry ͉ dentition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
169
3
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(183 citation statements)
references
References 47 publications
9
169
3
2
Order By: Relevance
“…Falk et al (2005a) note that human pygmy skulls typically have cranial capacities exceeding 1,000 cc (compared to a worldwide mean value for all modern humans of 1,349 cc) (Beals et al, 1984). The adult female pygmy skull used in their comparison in fact had a cranial capacity of 1,249 cc, while modern Rampasasa pygmies on Flores have an average cranial capacity of 1,270 cc (Jacob et al, 2006), similar to the value of 1,204 cc reported by Jacob (1967) for the Flores ''pygmoid'' described by Verhoeven (1958). explicitly suggested that Homo floresiensis was derived from Homo erectus through a process of insular dwarfing (see also Morwood et al, 2005b), although Morwood et al (2005a) state that ''H.…”
Section: Cranial Capacitymentioning
confidence: 99%
See 4 more Smart Citations
“…Falk et al (2005a) note that human pygmy skulls typically have cranial capacities exceeding 1,000 cc (compared to a worldwide mean value for all modern humans of 1,349 cc) (Beals et al, 1984). The adult female pygmy skull used in their comparison in fact had a cranial capacity of 1,249 cc, while modern Rampasasa pygmies on Flores have an average cranial capacity of 1,270 cc (Jacob et al, 2006), similar to the value of 1,204 cc reported by Jacob (1967) for the Flores ''pygmoid'' described by Verhoeven (1958). explicitly suggested that Homo floresiensis was derived from Homo erectus through a process of insular dwarfing (see also Morwood et al, 2005b), although Morwood et al (2005a) state that ''H.…”
Section: Cranial Capacitymentioning
confidence: 99%
“…1), the possibility of a pathological disorder, specifically some form of microcephaly, must be considered (Henneberg and Thorne, 2004;Jacob et al, 2006;Martin et al, 2006;Richards, 2006). This possibility was mentioned briefly in the original report , but then rejected.…”
Section: Skull In Human Microcephalicsmentioning
confidence: 99%
See 3 more Smart Citations